Finishing Beef - Dhuyvetter, Kevin C.; Langemeier, Michael (My University, 2012)
This publication helps a producer that buys feeder calves and then finishes them, and uses projected input and output prices for illustrative purposes to find the break-even price.
MF592_2012_01
Keywords: MF592; Economics; Livestock; MF